Impact Analysis of the Poverty Alleviation Acceleration Program in Paleleh District, Buol Regency, Indonesia - Amirudin Rauf; Fathurrahman; Patta Tope; Moh. Ahlis Djirimu (Research Horizon, 2022)
This study aimed to analyze the effect of the Poverty Alleviation Acceleration Program (P3K) on increasing the income of corn farmers in Paleleh District, Buol Regency, Central Sulawesi Province. This type of research was developmental studies, which aimed to find out the development of the subject. Respondents obtained for this research data were from corn farmers in Paleleh District, Buol Regency, Central Sulawesi Province. The data analysis method uses different tests. The analysis results show that the poverty alleviation acceleration program in Paleleh District, Buol, significantly influences corn farmers' income. The study results indicate that the poverty alleviation program implemented by the Paleleh district government, has a specificity in term of reducing processing costs. The results showed that the poverty alleviation acceleration program in Paleleh District, Buol, Central Sulawesi Province can be one of the steps in handling poverty alleviation of the community in the area. Furthermore, it is more likely to increase the income of corn farmers in Paleleh District, Buol Regency, Central Sulawesi Province.